Process Capability Indices for Processes when the Underlying Data are Interval-Valued - Ravichandran, J.; Santhosh, Deepa (International Journal of Statistics in Medical Research, 2024)
One of the important activities of process quality management is to see that the processes of interest are, in fact, stable and capable. In this paper, the problem of obtaining process capability indices (PCIs) for the processes when the underlying data are interval-valued is considered. Since interval-valued data such as systolic and diastolic readings have specifications for both lower and upper values, drawing PCIs cannot be straightforward. In this paper, we attempted to build connections between the lower and upper specifications limits based on which the resulting PCIs are drawn. This is done by considering the coefficients of inflation and the mean shift values of distributions of both lower and upper values of the interval-valued data. The new expressions for the proposed PCIs are determined. We have considered the systolic and diastolic data to demonstrate the computations of PCIs.